Penciptaan Tari Furshotu Tsaniyah Menggunakan Methods of Construction Jacqueline Mary Smith-Authard - Rahmat Suryo Samudro (Jurnal Pendidikan Tari, 2021)
"Furshotu Tsaniyah" is taken from Arabic, Al-Furshotu which means opportunity, opportunity comes, and At-Tsaniyatun which means second. Furshotu Tsaniyah means second chance. The interpretation of this title is that there is a second chance for those who feel alive again from near death and experience life after death. The dance work "Furshotu Tsaniyah" is based on the basic movements of Sundanese dance combined with contemporary movement techniques that are explored infinitely by the choreographer. Appointed this story into a dance work to give a moral message to the community through dance works. This dance work was created through the methods of construction Jacqueline Mary Smith-Authard which consists of methods of construction 1 - 8. The embodiment of the resulting dance work is in the form of dance compositions developed from processing Sundanese dance movements and contemporary movement techniques as well as supporting elements of dance works like angel wings and whips. The dance work "Furshotu Tsaniyah" uses a dramatic dance type with a single-cone dramatic design and presented in a symbolic presentation mode.